Efeitos do ensino informatizado na capacitação de professores para a execução de tentativas discretas com crianças com diagnóstico do Transtorno do Espectro Autista (TEA) - Valentim, Aline Santti (2018)
Autism Spectrum Disorder (ASD) is characterized as a limitation in social interaction and verbal behavior that occurs persistently in different contexts since early childhood and usually remains throughout individual’s life. Among intervention models for cases of ASD, behavioral therapy is one of the most effective. Studies have investigated alternative methods for teaching parents and professionals to apply discrete trial training (DTT) that would make possible to dispense or minimize the presence of a specialist and would be faster and more economical. Computer-assisted teaching is an alternative that has been investigated in different countries, although, until now, few studies have been carried out on computer-assisted teaching of discrete trial training in Brazil. The present study aimed to evaluate the effectiveness of a teaching instruction with discrete trial training performed in a fully computerized manner on the accuracy of teachers’ performance in the execution of discrete trial training. Three female teachers with experience in attending children with ASD from a special inland school of the Brazilian state of Paraná were the participants. The discrete trial training sessions were carried out with four children from the same school. Only one teacher completed all the modules. The applied computer-assisted teaching was not sufficient to enable the teachers to execute discrete trial training in the natural context, and the results did not show a correspondence between the teaching objectives of each module and changes in the teachers’ performances during discrete trial training sessions with the children with ASD. Finally, it was possible to list aspects that deserve future researches in the area of computer-assisted teaching of discrete trial training